Comparative study of the effects of biocides and metal oxide nanoparticles on microbial community structure in a stream impacted by hydraulic fracturing. (December 2021) - Alhajjar, Rehab K.; Ghannam, Ryan B.; Chen See, Jeremy R.; Wright, Olivia G.; Campa, Maria Fernanda; Hazen, Terry C.; Lamendella, Regina; Techtmann, Stephen M.
Abstract: Our study goal was to investigate the impact of biocides and nanoparticles (NPs) on the microbial diversity in a hydraulic fracturing impacted stream. Biocides and NPs are known for their antimicrobial properties and controlling microbial growth. Previous work has shown that biocides can alter the microbial community composition of stream water and may select for biocide-resistant bacteria. Additional studies have shown that nanoparticles can also alter microbial community composition. However, previous work has often focused on the response to a single compound. Here we provide a more thorough analysis of the microbial community response to three different biocides and three different nanoparticles. A microcosm-based study was undertaken that exposed stream microbial communities to either biocides or NPs. Our results showed a decrease in bacterial abundance with different types of nanoparticles, but an increase in microbial abundance in biocide-amended treatments. The microbial community composition (MCC) was distinct from the controls in all biocide and NP treatments, which resulted in differentially enriched taxa in the treatments compared to the controls. Our results indicate that NPs slightly altered the MCC compared to the biocide-treated microcosms. After 14 days, the MCC in the nanoparticle-treated conditions was similar to the MCC in the control. Conversely, the MCC in the biocide-treated microcosms was distinct from the controls at day 14 and distinct from all conditions at day 0. This finding may point to the use of NPs as an alternative to biocides in some settings. Graphical abstract: Image 1 Highlights: Biocides and nanoparticles are important tools for microbial control. Microbial abundance increased in biocide-treated microcosms and decreased in control and nanoparticles-treated microcosms. Biocides selected for a distinct microbial diversity relative to nanoparticles and control microcosms. Nanoparticle-treated microcosms had slightly altered microbial community compared to the control microcosm.